2002
DOI: 10.1093/carcin/23.7.1127
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the p16INK4 locus in human malignant mesothelial tumors

Abstract: The INK4 locus has two promoters and encodes two unique proteins that share exons in different reading frames, p16(INK4a) and p14(ARF). The p16(INK4a) protein, by inhibiting cyclin-dependent kinase, down regulates Rb-E2F and leads to cell cycle arrest in the G1 phase. The p14(ARF) protein interacts with the MDM2 protein, neutralizing MDM2-mediated degradation of p53. Since p53/Rb genes are not altered in malignant mesothelioma, additional components of these pathways, such as p16(INK4a) and p14(ARF), are candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 10 publications
4
92
0
Order By: Relevance
“…In our study, all pleural biopsies displaying reactive mesothelial proliferations in backgrounds of acute fibrinous pleuritis or chronic pleuritis were negative for 9p21 deletion, while the deletion was easily detected in a substantial number of mesotheliomas. The proportion of malignant mesothelioma demonstrating the 9p21 deletion in our study (67% for pleural and 25% for peritoneal) is similar to a PCR-based study reported by Hirao et al 35 who found homozygous deletion in 22% of 45 analyzed mesotheliomas. It is known that other alterations may occur at this locus that cannot be detected by FISH.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, all pleural biopsies displaying reactive mesothelial proliferations in backgrounds of acute fibrinous pleuritis or chronic pleuritis were negative for 9p21 deletion, while the deletion was easily detected in a substantial number of mesotheliomas. The proportion of malignant mesothelioma demonstrating the 9p21 deletion in our study (67% for pleural and 25% for peritoneal) is similar to a PCR-based study reported by Hirao et al 35 who found homozygous deletion in 22% of 45 analyzed mesotheliomas. It is known that other alterations may occur at this locus that cannot be detected by FISH.…”
Section: Discussionsupporting
confidence: 91%
“…In the same study, 9% of malignant mesotheliomas were found to have promoter hypermethylation and 2% were found to harbor a point mutation of the p16 gene. 35 We did not explore these two genetic alterations in our study because a different technical approach would be needed, but these alterations may have existed in cases included in our study. We chose to use FISH analysis in our study for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…80 One of the most common genetic alterations in mesothelioma is the homozygous deletion of the 9p21 locus within a cluster of genes that includes cyclin-dependent kinase inhibitor 2A (CDKN2A), CDKN2B, and methylthioadenosine phosphorylase (MTAP). [81][82][83][84][85] Several cytogenetic and molecular studies have reported p16/CDKN2A deletions in up to 80% of primary pleural mesotheliomas, depending on the histologic subtype (90%-100% of sarcomatoid mesothelioma, 70% of epithelioid and mixed types). In contrast, this deletion occurs in approximately 25% of peritoneal mesotheliomas.…”
Section: Bg8mentioning
confidence: 99%
“…6 Homozygous deletions of the INK4a/ARF locus, however, have been shown to be the predominant events that occur at a frequency of Ͼ 70% in this malignancy. [7][8][9] This deletion results in the loss of p14 ARF , in the increase of MDM2, and in the functional inactivation of p53, thereby diminishing the p53 response to genotoxic stress. 10,11 It was reported previously that the p14 ARF transfection resulted in apoptotic cell death through the induction of p14 ARF overexpression.…”
Section: T Rmentioning
confidence: 99%